2022
DOI: 10.1016/j.jpainsymman.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Adolescent Perspectives on the Impact of COVID on the Care of Seriously Ill Children

Abstract: Context : Few studies have explored the impact of the Coronavirus Pandemic (COVID-19) on the care of seriously ill children which may be especially affected due to the child's vulnerability, complexity of care, and high reliance on hospital-based care. Objective : To explore parental and adolescent perspectives on the impact of COVID-19 on care of seriously children. Methods : We recruited a convenience sample of families of seriously ill chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Despite the barriers created by COVID-19, the use of virtual technology to meet care requirements while maintaining social distancing restrictions was beneficial for our cohort. This finding aligns with other studies demonstrating the value of virtual care and telemedicine in the care of CMC and other paediatric populations [ 10 , 33 , 34 ]. The use of virtual healthcare can mitigate geographical barriers and financial costs associated with in-person visits such as parking fees and gas expenses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the barriers created by COVID-19, the use of virtual technology to meet care requirements while maintaining social distancing restrictions was beneficial for our cohort. This finding aligns with other studies demonstrating the value of virtual care and telemedicine in the care of CMC and other paediatric populations [ 10 , 33 , 34 ]. The use of virtual healthcare can mitigate geographical barriers and financial costs associated with in-person visits such as parking fees and gas expenses.…”
Section: Discussionsupporting
confidence: 92%
“…Visitor restrictions resulted in family separation and lack of support, which was challenging for families during high-stress periods. In another qualitative study examining the implications of pandemic safety measures, parents of seriously ill children noted feeling more isolated and burnt-out during hospital admissions and clinic visits due to visitor restrictions in medical facilities [ 33 ]. In keeping with these findings, several FCs in our study highlighted the difficulties in attending in-hospital appointments as a sole caregiver and recommended allowing more than one caregiver to accompany CMC in hospital at all times.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to open parent visiting, with provision for overnight stays, only one parent could be designated to be with their child at any time during admission in the early months of the pandemic. This disruption to caring for children as a family unit has also been reported in other studies which have, in addition, included data from parental perspectives alongside professionals 23. In a study from the USA, parents who were able to be with their child also reported less contact with clinical staff, reducing information exchange opportunities in comparison with their prepandemic hospital experience, a change acknowledged by clinicians.…”
Section: Discussionmentioning
confidence: 52%
“…Another difference among our sample is that, whereas clinicians largely saw parent coaching as a “net positive,” caregiver experiences were more nuanced. For example, although many parents, after a transition period, appreciated and felt empowered by parent coaching, they also felt the strain of “having to do everything.” Little is known about parental burnout with remote therapies and schooling, but recent research suggests that a hybrid model, with flexibility for in-person and telehealth options, may support parents’ mental health (Beight et al, 2022; Kerr et al, 2021). Clinician burnout, however, is receiving much more attention, 1 in light of health care provider shortages nationally (Shin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%